Delivery outcomes in subsequent pregnancy following primary breech cesarean delivery: a retrospective cohort study. (2nd May 2020) - Eden-Friedman, Yehudit; Ginosar, Yehuda; Sela, Hen Y.; Calderon-Margalit, Ronit; Eventov-Friedman, Smadar; Ezra, Yossef; Weiniger, Carolyn F.
Abstract: Background : Women may be unaware of the potential impact on subsequent deliveries of the decision to undergo primary breech cesarean (PBC) delivery rather than attempt external cephalic version (ECV). We investigated cesarean delivery rates and adverse maternal outcomes in the subsequent delivery following management of breech presentation by ECV versus PBC. Methods: This retrospective study identified women who delivered subsequent to breech presentation managed by attempted ECV or PBC. We assessed cesarean delivery rates and adverse maternal outcomes including hemorrhage, placental complications, infection, and obstetric complications in the subsequent delivery following attempted ECV versus PBC. Results: We identified 307 women who had attempted ECV and 508 with PBC in the index breech pregnancy. Following attempted ECV, 47 (15.3%) women had cesarean delivery in the subsequent pregnancy versus 246 (48.4%) following PBC, adjusted OR 0.24, 95% CI 0.16–0.35 for subsequent cesarean delivery after attempted ECV in the index pregnancy. The frequency of composite adverse outcomes related to cesarean delivery was 30 (9.8%) following attempted ECV versus 104 (20.5%) after PBC, p < .0001. The frequency of composite severe adverse maternal outcome was similar following attempted ECV 25 (8.8%) versus PBC 59 (11.9%). Conclusions: The current study suggests that attempted external cephalic version was associated with a five-fold decrease risk to undergo cesarean in the subsequent delivery and a significantly decreased frequency of composite adverse outcomes related to cesarean delivery in the subsequent delivery.